2021
DOI: 10.3390/biom11121810
|View full text |Cite
|
Sign up to set email alerts
|

microRNA Biomarkers in Clinical Study

Abstract: MicroRNAs (miRNAs), short non-coding RNAs, are involved in the initiation and progression of many human diseases that also play a key role in immune response and drug metabolism modulation [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…It is reported that non-protein coding genes transcribe approximately 50% of the miRNAs expressed in the human genome and are coded in the introns of coding genes (Ardekani and Naeini, 2010). Human diseases develop and progress are impacted by miRNAs, which are also crucial for regulating drug metabolism and immune responses (Wang and Chen, 2021). MicroRNAs regulate cellular functions such as growth, development, differentiation, metabolism, and immune responses.…”
Section: Functions Of Micrornasmentioning
confidence: 99%
“…It is reported that non-protein coding genes transcribe approximately 50% of the miRNAs expressed in the human genome and are coded in the introns of coding genes (Ardekani and Naeini, 2010). Human diseases develop and progress are impacted by miRNAs, which are also crucial for regulating drug metabolism and immune responses (Wang and Chen, 2021). MicroRNAs regulate cellular functions such as growth, development, differentiation, metabolism, and immune responses.…”
Section: Functions Of Micrornasmentioning
confidence: 99%